2013
DOI: 10.1021/jf402774d
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Thermal Deglycosylation of Ginsenoside Rd and Its Contribution to the Improved Anticancer Activity of Ginseng

Abstract: The root of ginseng is a famous functional food and a herbal medicine. Research into the development of a method for increasing the pharmaceutical effect of ginseng by conversion of ginsenosides, the major active components of ginseng, by high-temperature and high-pressure thermal processing has been conducted. However, changes in the structures of each ginsenoside by heat processing and their contributions to anticancer activity have not yet been fully elucidated. Here, we investigated whether anticancer acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 16 publications
(26 reference statements)
1
69
0
Order By: Relevance
“…11,18,19 Ginsenoside Rg3 is converted to Rg5 and Rk1 by further dehydration at the carbon-20 position by high pressure and temperature. 13,19 Using LLC-PK1 renal epithelial cells as the in vitro model, we compared the protective activities of WG, MG, MG−MeOH, MG−H 2 O, ginsenoside Rg3 epimers, and ginsenoside Rg5/Rk1 against cisplatin-induced oxidative renal damage. The ginsenoside stereoisomers were used as mixtures because of the difficulty in preparing a single ingredient with high purity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,18,19 Ginsenoside Rg3 is converted to Rg5 and Rk1 by further dehydration at the carbon-20 position by high pressure and temperature. 13,19 Using LLC-PK1 renal epithelial cells as the in vitro model, we compared the protective activities of WG, MG, MG−MeOH, MG−H 2 O, ginsenoside Rg3 epimers, and ginsenoside Rg5/Rk1 against cisplatin-induced oxidative renal damage. The ginsenoside stereoisomers were used as mixtures because of the difficulty in preparing a single ingredient with high purity.…”
Section: Resultsmentioning
confidence: 99%
“…Ginsenosides were identified and quantified using a previously reported method. 13 An analytical reversedphase HPLC system comprised of a solvent degasser (Agilent, G1322A), binary pump (Agilent, G1312C), and model 380 evaporative light scattering detector (ELSD, Agilent) was used in the analysis. The standard solutions containing 1−100 μg of each ginsenoside were injected onto the HPLC column, with all calibration curves showing good linearity (R 2 > 0.995).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological studies on ginsenosides have reported neuroprotective, anti-HIV, antioxidant and anticancer effects. [23][24][25] The major active components ginsenosides that was used in traditional Chinese medicine has been proved to be antioxidants against AAPH-induced hemolysis of erythrocytes. 26) In the previous study, many dammarane-type derivatives have been prepared and investigated for their activities.…”
Section: -7)mentioning
confidence: 99%
“…As secondary metabolite compounds, the minor ginsenosides have some chemical reactivity that the major ginsenosides do not. Furthermore, there is emerging evidence that the minor ginsenosides have more important pharmaceutical effects, such as anti-cancer, anti-diabetic, anti-oxidative, and anti-aging effects, than the glycosylated major ginsenosides [10], [11], [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%